Magneto-bioconvection flow of hybrid nanofluid in the presence of oxytactic bacteria in a lid-driven cavity with a streamlined obstacle - Hussain, Shafqat; Aly, Abdelraheem M.; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2022)
This work explores the magneto-bioconvection flow of silver(Ag)-magnesium oxide(MgO)-water hybrid nano-liquid in a porous cavity considering the effect of gyrotactic microorganisms. The novelty of this work is to examine the magnetic force on bioconvection flow in a porous cavity containing obstacle, oxytactic bacteria and occupied by a hybrid nanofluid. A streamlined square obstacle is inserted in the flow field. For the modeling of porous medium, Brinkman-Forchheimer extended Darcy's model is considered. In order to simulate the gov-erning system of dimensionless equations, a higher Galerkin finite element method (GFEM) is implemented. The resulting discrete algebraic systems are treated using the adaptive Newton's method. The validity and reliability of designed solver is ensured by recomputing the numerical and experimental data available in the literature. The flow structure, heat and mass transport are analyzed for the controlling parameters such as Hartmann number (H-a = 0 -100), bioconvection Rayleigh number (R-b = 10 -100), Peclet number (P-e = 0.1 -1), Richardson number (R-i = 0.1 -5), Lewis number (L-e = 1 -10) and Darcy number (Da = 10-5 -10-2). The obtained numerical approximations demonstrated that the variation of heat transfer becomes almost constant for varying the Peclet number. Whilst the Sherwood number is a decreasing function of Peclet number. The dimensions of streamlined obstacle can serve as a control parameter and it makes opposite impact on heat and mass transport.
Keywords: Porous cavity; Ag/MgO-water hybrid nanofluid; Horizontal magnetic field; Oxytactic bacteria; Streamlined obstacle; Higher order GFEM